Study of Functions in the Process of Playing the Te'dek Flute at the Solo Sign Ceremony in North Toraja (Universitas Negeri Semarang, 2022)
Rambu Solo' is a death ritual ceremony performed in Toraja and centered on the beliefs of the Toraja tribe's ancestors or commonly called Aluk To'dolo. The implementation of the ceremony almost always involves performing arts. One of the types of artistic offerings displayed is the Suling Te’dek. Suling Te’dek is one of the traditional musical instruments in Toraja and is a type of wind instrument made from traditional materials, namely in Toraja terms it is called Bambu Bulo which has been used for generations by the Toraja people in every mourning ceremony. The author aims to analyze how the process of playing Suling Te’dek in the Rambu Solo' ceremony. This study of traditional musical instruments by researchers using qualitative research with data analysis through observation, interviews and procurement of documentation. The results of the research show that the Suling Te’dek in the playing process is played together with Marakka singing (singing with Toraja language poetry/vocal music). The form of presenting Suling Te’dek music includes playing melodies which sometimes follow the melodies of Marakka's singing. However, until now there is no specific scale or patent used in Toraja. So the author in describing the scales for a while is to write them into the arrangement of the types of melodies that are often played in the musical presentation, namely Do, Di, Re, Mi, Sol, La as the arrangement of notations in Suling Te’dek. Keywords: function, Suling Te’dek, game process, Rambu Solo’, Toraja Utara